Analisis Yuridis Putusan Hakim dalam Menjatuhkan Sanksi Pidana terhadap Pelaku Pencurian dengan Pemberatan Tabung Gas Elpiji (Studi Putusan Nomor 813/Pid.B/2025/PN Rap) - Silvana Herman, Muhammad Yusuf Siregar Wahyu Simon Tampubolon, Indra Kumalasari (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the judge's considerations in the Rantauprapat District Court Decision Number 813/Pid.B/2025/PN Rap regarding the crime of aggravated theft committed by the defendant FAM against two 3 kg LPG gas cylinders. The research method used is normative juridical with a statutory approach and decision study. The results of the study indicate that the Public Prosecutor demanded a six-month prison sentence for the defendant based on Article 363 paragraph (2) of the Criminal Code, while the panel of judges sentenced him to five months' imprisonment. The decision was based on the fulfillment of all elements of aggravated theft, especially because the act was committed at night, in collaboration, and by damaging and climbing the victim's house. However, from the perspective of substantive justice, this decision raises the issue of injustice considering that the value of the victim's loss is relatively small and is below the limit of IDR 2,500,000 as stipulated in Supreme Court Regulation Number 2 of 2012 concerning Adjustment of the Limits for Minor Crimes, which opens up space for non-imprisonment settlements. Thus, this study concludes that although the judge's decision has fulfilled legal certainty, there remains a tension between the application of formal law and the principles of justice and expediency in cases of petty crimes motivated by economic motives.